Student learning venture overseas in the transnational research partnership – a Taiwan and US PIRE case study - Angela Yung Chi Hou; Sheng-Ju Chan; Lily Lin; Zoe Hu (Higher Education Evaluation and Development, 2020)
Purpose – Transnational learning has become a mainstream issue in recent years due to the rise of global education. There are many kinds of overseas learning, including degree-seeking, joint/double degree, student exchange, internship, service learning and so on. The scope of learning may involve research, teaching/learning and community service. The purpose of the case study is to investigate how the Taiwanese students participating in an international internship project of the US–Taiwan Partnerships for International Research and Education (PIRE) acquire professional knowledge and soft skills, including cross-cultural awareness, interdisciplinary communication, skill development and social networking. It also explores how a joint research project contributes into a collaborative educational program. Design/methodology/approach – To better understand participants' experiences in the PRIE, this study held three focus groups and seven in-depth interviews on the students, faculty members and project managers for data collection. Findings – Three major findings are shown in the study. First, participants agreed that the overall learning experiences in knowledge acquisition or skill development have been positive. Second, participants obviously expressed their greater interests in intercultural interaction with the locals, which did not happen quite often during the internship. Third, the extent of interest in applying for the PIRE deg ree program after the internship program is escalating year by year. Research limitations/implications – More investigation into participants’ social and cultural engagement in similar project will be needed for future research. Practical implications – The results will be implicated into other cross-border education project evaluation. Originality/value – This study manages to investigate the cross-border research initiative from different participants' perspectives and received comprehensive feedbacks.